(untitled) (Indian Journal of Arid Horticulture, 2025)
The field trials were conducted for management of Alternaria leaf blight (Alternaria cucumerina var. P. watermelon) in mateera (watermelon) by fungicides, bio-agents and botanical during summer season of 2013 and 2014 at Plant Pathology Block of ICAR-Central Institute for Arid Horticulture, Bikaner (Rajasthan). Three fungicides (copper oxychloride, carbendazim and mancozeb), four bio-agents (Aspergillus niger, Pseudomonas fluorescens CIAH-196, Trichoderma viride CIAH-240 and Trichoderma viride Non-Resistant) and one botanical such as onion leaf extract were taken for the study. Disease incidence and disease severity of Alternaria leaf blight in mateera ranged from 10.0 to 34.17% and 8.88 to 29.01%, respectively. Among nine treatments, one foliar spray of mancozeb (0.25%) proved the most effective fungicide for the management of this disease in mateera under field conditions with the minimum disease incidence (10.0%) and disease severity (8.88%) and the maximum disease control (69.39%). Further, next best treatment was Trichoderma viride CIAH-240 (5%). However, the maximum disease incidence (34.17%) and disease severity (29.01%) were observed in control followed by onion leaf extract (5%) with disease incidence (27.85%), disease severity (24.34%) and the minimum disease reduction (16.09%).